Case Study: Design of Public Policies in the Face of Climate Change - Gómez Sánchez Soto, Rubén (2024)
The design of public policies in the face of climate change” seeks to identify the relationships between several key elements; such as public administration, governance, public policies, results of improvements in the face of climate change, economic growth and more. It is necessary to review what the United Nations and its international organizations point out: “Climate change refers to long-term changes in temperatures and weather patterns” and among its most important impacts are: higher temperatures, intense storms, increased drought, a warming and rising ocean, food shortages, increased health risks, poverty and displacement. This premise supports the effort that nations need to make to improve their governance capacities expressed in their public policies regarding the treatment of climate change. Regarding the mission of the public administration: “Carry out adequate governance of the data managed by the administration through transversal policies to obtain the highest performance from them both internally and on the part of citizens, in the form of economic value and social". For this reason, it highlights the need to reflect and investigate the importance of proposing a model for the design and formulation of public policies in the face of climate change. This last need involves rethinking governance actions and the design of public policies so that public administrations can fulfill their mission.